Book Review - Rus, Thomas R. (Columbia Journal of Environmental Law, 2020)
NORMAL ACCIDENTS: LIVING WITH HIGH-RISK TECHNOLOGIES. By Charles Perrow. New York, N.Y.: Basic Books, 1984. Pp. x, 386. Cloth $21.95.